1973
DOI: 10.1063/1.1680607
|View full text |Cite
|
Sign up to set email alerts
|

Reorientational and angular momentum correlation times in gaseous tetrafluoromethane at moderate densities

Abstract: NMR 19F spin-lattice relaxation times and Raman 435 cm-I doubly degenerate [v,(e)] vibrational-rotation band shapes have been measured in gaseous carbon tetrafluoride at 25·C and densities of 9 to 120 amagat. NMR spin-lattice relaxation times have also been measured over the temperature range of -60 to 4O·C for the above densities. The Fourier transform analysis of the Raman band shapes has allowed us to calculate the reorientational correlation time T6>" Since spin rotation interactions provide the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Also shown are the results from 19 F relaxation experiments on CF 4 . 63 For CF 4 , the extended diffusion model agrees very well with experiment.…”
Section: Comparison With Reorientation Modelssupporting
confidence: 70%
“…Also shown are the results from 19 F relaxation experiments on CF 4 . 63 For CF 4 , the extended diffusion model agrees very well with experiment.…”
Section: Comparison With Reorientation Modelssupporting
confidence: 70%
“…Particularly, for the dipolar, quadrupolar, and spin-rotation relaxation the relevant interaction strengths are determined by the gyromagnetic ratios of the proton and the deuteron, the quadrupole moment of the deuteron, and spin-rotation constants of the HD molecule, respectively. When considering the gas phase, the correlation time for changes of the angular momentum vector and the correlation time for molecular reorientation are positively correlated [26], and at sufficiently high pressure the relaxation time is directly proportional to the gas density [27][28][29]. Indeed, a series of experiments conducted by Beckmann et al [30] confirmed that the minimum T 1 dependence on pressure is approximately 0.5 bar for molecular hydrogen.…”
Section: Analysis Of 1 H and 2 H Nmr Line Shapes Of Hdmentioning
confidence: 71%